Sociocultural Context of the Yoruba Religion in Cuba: Cultural Legacy of the Transculturation Process - Baby-Ramírez, Yousy; Gutiérrez-Gómez, Edgar; Janampa-Patilla, Hubner; Munaris-Parco, Sonia Beatriz (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2025)
The national cultures of Latin America and the Caribbean owe an important part of their historical formation to the settlement of enslaved Africans during the XVI - XIX centuries. The religions of African antecedents in Cuba constitute hard nuclei of cultural resistance, where the process of transculturation has left its mark. The study analyzes diverse epistemological positions of some researchers, as well as oral testimonies of religious and practitioners. The research is based on a systematic review with a critical approach based on the method of analysis and synthesis. The results offered reveal that religions of African origin have contributed significantly to the development of Latin American and Caribbean cultural identity. The resurgence of the Yoruba religion in Cuba is an example of the cultural legacy inherited from the transculturation process and passed down from generation to generation, enduring over time.